EBF1 gene polymorphism and its interaction with smoking and drinking on the risk of coronary artery disease for Chinese patients. Issue 3 (21st June 2018) - Ying, Yongjun; Luo, Yuxuan; Peng, Hui
Abstract : Objective : Early B-cell factor 1 (EBF1) is a transcription factor that is expressed in early B-cells, adipocytes, and olfactory neurons, and is essential for the maturation of early B lymphocytes. The present study analyzes the influence of EBF1 gene polymorphism and its interaction with smoking and drinking on the risk of coronary artery disease (CAD).Methods: In the present study, 243 CAD cases were enrolled as the CAD group and 215 non-CAD patients as the control group by case–control study. We analyzed their genotypes of the rs987401919, rs36071027, and rs1056065671 loci of the EBF1 gene by Sanger sequencing and detected their content of HDL-C, LDL-C, and TG.Results: The C allele at the rs987401919 and rs36071027 loci of EBF1 was found to be the risk factor for CAD (Odds ratio, OR = 1.233; 95% confidence interval, CI: 1.039–1.421; P =0.017; OR = 1.487; 95% CI: 1.015–1.823; P =0.042). The interaction between single nucleotide polymorphisms (SNP) of the rs987401919 and rs36071027 loci and smoking and drinking were distinctly associated with the incidence of CAD ( P <0.05). The content of systolic blood pressure (SBP), diastolic blood pressure (DBP), HDL-C, LDL-C, and TG was distinctly changed after gene mutation at the rs987401919 and rs36071027 loci ( P <0.05).Conclusion : The results of the present study show that the mutation (CT+TT) at the rs987401919 and rs36071027 loci of EBF1 and its interaction with smoking and drinking are risk factors for CAD, and that the mechanism may be related to the changes in blood pressure and blood lipid content.